Microwave ablation in porcine livers applying 5-minute protocols: influence of deployed energy on extent and shape of coagulation - Sommer, Christof-Matthias; Bryant, Mark; Kortes, Nikolas; Stampfl, Ulrike; Bellemann, Nadine; Mokry, Theresa; Gockner, Theresa; Kauczor, Hans-Ulrich; Radeleff, Boris (Journal of vascular and interventional radiology, 2012)
Purpose: To evaluate the influence of deployed energy on extent and shape of microwave (MW)-induced coagulation in porcine livers applying 5-minute protocols. Materials and Methods: MW ablations (n = 25) were performed in ex vivo porcine livers (n = 8). Ablation time was 5 minutes. Five study groups were defined, each with different power output: I, 20 W (n = 5); II, 40 W (n = 5); III, 60 W (n = 5); IV, 80 W (n = 5); and V, 105 W (n = 5). Extent and shape of white coagulation was evaluated macroscopically, including short diameter, volume, front margin, coagulation center (distance between center of short diameter of coagulation and applicator tip), and ellipticity index (short diameter/long diameter). Deployed energy was also analyzed. Results: Short diameter and volume were significantly different (P<.001 and P<.001) between the groups: I, 23.0 mm and 11.1 cm3; II, 12.4 mm and 12.4 cm3; III, 27.0 mm and 17.6 cm3; IV, 31.0 mm and 29.2 cm3; and V, 35.0 mm and 42.3 cm3. Front margin and coagulation center were also significantly different (P<.05 and P<.001): I, 6.0 mm and 13.0 mm; II, 8.0 mm and 11.0 mm; III, 8.0 mm and 14.0 mm; IV, 8.0 mm and 18.0 mm; and V, 10.0 mm and 19.0 mm. Ellipticity index was not significantly different. Deployed energy was significantly different (P<.001): I, 5.7 kJ; II, 11.0 kJ; III, 15.5 kJ; IV, 21.6 kJ; and V, 26.6 kJ. Conclusions: Extent, but not shape, of MW-induced coagulation depends on the deployed energy. Applying the protocols described in this study, significantly different coagulation volumes can be created with an ablation time of 5 minutes but different power output.